Automatic attendance system using facial recognition - Sikdar, Tushar; Binte Amin, Nafia; Shupti, Ayesha Akter; Ferdous, A.K.M Zubaer; Dashgupta, Amit (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.